Tailoring Surface‐Confined Nanopores with Photoresponsive Groups1. Issue 32 (26th June 2013) - Tahara, Kazukuni; Inukai, Koji; Adisoejoso, Jinne; Yamaga, Hiroyuki; Balandina, Tatyana; Blunt, Matthew O.; De Feyter, Steven; Tobe, Yoshito
<x xml:space="preserve">Abstract</x> Opening light: Two‐dimensional pores are formed by the self‐assembly of azobenzene‐functionalized triangular building blocks on graphite at the liquid–solid interface. These pores can selectively host a guest molecule. The pore size can be reversibly changed by irradiation at different wavelength which changes the number of guest molecules that are adsorbed (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>